Utilizing Drama as a Pedagogical Tool for the Instruction of Civic Education in Public Primary Schools within Cross River State: An Analysis of St. Christopher's Primary School Abuochiche, Bekwarra - Obukoadata, Presly Ruke; Emuru, Linus Ejunka; Kalita, Aruku Joseph; Eric, Ogri Omari; Ochuole, Odey Helen (ALSYSTECH Journal of Education Technology, 2024)
The study examined the effectiveness of using drama as a teaching technique for Civic Education in primary schools in Cross River State. The main objective was to see how drama could be used in the early education of young learners. The study used survey research with purposive sampling, involving twenty-seven participants from St. Christopher's Primary School Abuochiche. Data was collected using a structured questionnaire in a four-point Likert format and analyzed using weighted mean scores and frequency tables. The results show that using drama can significantly improve the teaching of Civic Education, enhance communication skills, and build confidence in students, especially when teachers participate in the performances. The study concludes that incorporating dramatic displays into lessons may lead to better comprehension of various subjects in primary schools in Cross River State and recommends using drama not only for Civic Education but also for other subjects in primary schools throughout Nigeria.